2003
DOI: 10.1212/wnl.61.4.515
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral motor cortex disinhibition in complex regional pain syndrome (CRPS) type I of the hand

Abstract: al. The glycophospholipid-linked folate receptor internalizes folate without entering the clathrin-coated pit endocytotic pathway. J Cell Biol 1990;110:637-649. 42. Spector R, Lorenzo A. Folate transport in the central nervous system. Am J Physiol 1975;229:777-782. 43. Spector R. Micronutrient homeostasis in mammalian brain and cerebrospinal fluid. J Neurochem 1989;53:1667-1674. 44. Weitman SD, Weinberg AG, Coney LR, et al. Cellular localization of the folate receptor: potential role in drug toxicity and folat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
148
1
14

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 253 publications
(174 citation statements)
references
References 49 publications
11
148
1
14
Order By: Relevance
“…The analgesic effect of M1 tDCS could be related to the mechanisms of chronic pain in patients with SCI, such as central sensitization and deficient inhibitory process, as observed in previous tDCS studies focusing on pain management [33][34][35]. In a previous longitudinal study, the majority of SCI patients reporting chronic pain had their pain onset within six weeks post-injury and 80% of them stated that their pain started on the day of the injury [36].…”
Section: Tdcs To Prevent the Mechanisms Of Chronic Painmentioning
confidence: 71%
“…The analgesic effect of M1 tDCS could be related to the mechanisms of chronic pain in patients with SCI, such as central sensitization and deficient inhibitory process, as observed in previous tDCS studies focusing on pain management [33][34][35]. In a previous longitudinal study, the majority of SCI patients reporting chronic pain had their pain onset within six weeks post-injury and 80% of them stated that their pain started on the day of the injury [36].…”
Section: Tdcs To Prevent the Mechanisms Of Chronic Painmentioning
confidence: 71%
“…42 In addition, intra-cortical inhibition has been found to be decreased in the motor cortex contralateral to the affected limb or bilaterally. 38,40 Interestingly, in one study this reduction in intra-cortical inhibition of the motor cortex contralateral to the affected limb was linked with pain severity. 38 Consistent with this decreased inhibition, an fMRI study showed greater activation within the motor cortex (among other regions) during a fingertapping task performed with the affected hand relative to activations for the unaffected hand or activations seen in healthy controls.…”
Section: Complex Regional Pain Syndrome and Motor Reorganizationmentioning
confidence: 99%
“…38,40 Interestingly, in one study this reduction in intra-cortical inhibition of the motor cortex contralateral to the affected limb was linked with pain severity. 38 Consistent with this decreased inhibition, an fMRI study showed greater activation within the motor cortex (among other regions) during a fingertapping task performed with the affected hand relative to activations for the unaffected hand or activations seen in healthy controls. 62 Moreover, the degree of activation within the motor cortex was correlated with the amount of motor impairment evaluated during reach-to-grasp movements.…”
Section: Complex Regional Pain Syndrome and Motor Reorganizationmentioning
confidence: 99%
“…What's more, previous data suggest that pain would inhibit, rather than enhance, motor cortex excitability (Farina et al, 2001;Le Pera et al, 2001). A recent TMS study reported motor cortex disinhibition in patients with complex regional pain syndrome of the hand (Schwenkreis et al, 2003), a clinical condition which represent a model of chronic pain related to neurogenic inflammation. These Authors reported bilateral reduction of ICI, while unilateral hyperexcitability to paired-TMS was found in our group of patients.…”
Section: Mechanisms Of Motor Cortex Hyperexcitabilitymentioning
confidence: 99%